(untitled) (Journal of the College of Basic Education, 2022)
The importance of the research included in identifying the effect of stretching exercises that are practiced after aerobic exercises on the muscles of the lower extremity affected by muscle spasticity and the psychological relief of trainees aged 30-40 years. And the research problem lies in the fact that most people do not exercise stretching exercises after exercise, and this provides a great opportunity to face muscle pain and may tear, in addition to the failure of the performer of the exercises to feel full psychological comfort. The research objectives also included preparing stretching exercises that fit the capabilities of the research sample. And the identification of the effect of stomach stretching exercises on the lower limb muscles affected by muscle spasticity and the psychological relief of trainees aged 30-40 years. The researcher also used the experimental approach with the design of one group by pre and post testing on a sample of women aged (30 - 40) years who attend the Miss Gym with (5) trainees. The researcher conducted the tribal physical and psychological tests on Sunday 10/27/2019 and after the completion of the implementation of a set of prepared stretching exercises over a period of 8 weeks and with three training units per week, physical and psychological post tests were conducted for the research sample on Monday 23/12/2019, and after that, Processing the data statistically, so the researcher reached the following: Conclusions: Stretching exercises prepared by the researcher have a great effect on increasing muscle flexibility and treating muscle spasticity injury of the lower extremities. Aerobic exercises, in addition to stretching exercises, improved the state of personal psychological comfort and increased its level.